Long-term Follow-up of In-stent Stenosis After Pipeline Flow Diversion Treatment of Intracranial Aneurysms. Issue 6 (20th November 2016) - John, Seby; Bain, Mark D.; Hui, Ferdinand K.; Hussain, M. Shazam; Masaryk, Thomas J.; Rasmussen, Peter A.; Toth, Gabor
Abstract: BACKGROUND: There is scant information on in-stent stenosis after flow diversion treatment of intracranial aneurysms with the Pipeline Embolization Device (PED). OBJECTIVE: To assess the incidence, severity, nature, and clinical consequences of in-stent stenosis on angiographic follow-up after treatment with the PED. METHODS: A retrospective study of patients who underwent aneurysm treatment with the PED was conducted. In-stent stenosis was assessed on subsequent follow-up angiography. Intimal hyperplasia was defined as a uniform growth process beyond the limits of the metallic mesh at <25%. In-stent stenosis represented an area of parent vessel narrowing, most often focal, graded as mild (25%-50%), moderate (50%-75%), or severe (>75%). RESULTS: Between June 2011 and April 2015, 80 patients were treated with the PED. Angiographic follow-up was available for 51 patients (representing 76% of available or 64% of all patients). Mean follow-up was 12.5 months. In-stent stenosis was detected in 5 patients (9.8%) at a median of 6 months. Stenosis was mild in 4 of 5 (80%) and moderate in 1 of 5 (20%) patients. There were no cases of severe stenosis. No stenosis caused flow limitation, clinical symptoms, or required re-treatment. Additional follow-up angiography was available in 2 of 5 stenosis patients showing marked improvement. Sixteen patients (31%) had intimal hyperplasia, and 28 patients (55%) had no stenosis. Asymptomatic stent occlusion occurred in 2 patients (4%) related to medication noncompliance. CONCLUSION: Treatment with the PED was associated with a 9.8% rate of in-stent stenosis, detected on first angiographic follow-up, at a median of 6 months. None were symptomatic or required re-treatment, and they showed significant improvement on follow-up.